Post-Treatment Plasma D-Dimer Levels Are Associated With Short-Term Outcomes in Patients With Cancer-Associated Stroke - Nakajima, Sho; Kawano, Hiroyuki; Yamashiro, Kazuo; Tanaka, Ryota; Kameda, Tomoaki; Kurita, Naohide; Hira, Kenichiro; Miyamoto, Nobukazu; Ueno, Yuji; Watanabe, Masao; Hirano, Teruyuki; Fujimoto, Shigeru; et al. (Frontiers in Neurology, 2022)
Background and Objective: Hypercoagulability is associated with increased risks of ischemic stroke and subsequent mortality in patients with active cancer. This study investigated the relationships between plasma D-dimer levels after stroke treatment and short-term outcomes in patients with cancer-associated stroke. Methods: This retrospective, observational, multicenter study analyzed consecutive patients with cancer-associated ischemic stroke. Hypercoagulability was assessed by plasma D-dimer levels before and after stroke treatment. Short-term outcomes were assessed in terms of poor outcomes (a modified Rankin Scale score >3), cumulative rates of recurrent ischemic stroke, and mortality at 30 days after admission. Results: Of 282 patients, 135 (47.9%) showed poor outcomes. Recurrent ischemic stroke was observed in 28 patients (9.9%), and the cumulative mortality rate was 12.4%. Multivariate analysis showed that post-treatment plasma D-dimer levels ≥10 μg/ml were independently associated with both poor outcomes (adjusted odds ratio [OR], 9.61; 95% confidence interval [CI], 3.60–25.70; P < 0.001) and mortality (adjusted OR, 9.38; 95% CI, 3.32–26.44; P < 0.001). Pre-treatment plasma D-dimer levels ≥10 μg/ml were not associated with these outcomes. Patients who received heparin had higher pre-treatment plasma D-dimer levels than those treated with other anticoagulants. Heparin produced a significant reduction in D-dimer levels from pre- to post-treatment without increasing the incidence of hemorrhagic events. Conclusion: A high plasma D-dimer level after stroke treatment was associated with poor short-term outcomes in patients with cancer-associated stroke. Using anticoagulants to reduce D-dimer levels may improve short-term outcomes in these patients.